2016
DOI: 10.1371/journal.pone.0166565
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-Induced Effects on Nicotinic Acetylcholine Receptors (nAChRs), Ca2+ and Brain-Derived Neurotrophic Factor (BDNF) in STC-1 Cells

Abstract: In addition to the T2R bitter taste receptors, neuronal nicotinic acetylcholine receptors (nAChRs) have recently been shown to be involved in the bitter taste transduction of nicotine, acetylcholine and ethanol. However, at present it is not clear if nAChRs are expressed in enteroendocrine cells other than beta cells of the pancreas and enterochromaffin cells, and if they play a role in the synthesis and release of neurohumoral peptides. Accordingly, we investigated the expression and functional role of nAChRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 66 publications
(104 reference statements)
0
13
0
Order By: Relevance
“…Although, the vast majority of the antibodies against nAChR subunits are considered to lack specificity [ 29 , 30 ], in this study nAChR expression in TRCs was confirmed by qRT-PCR, ISH and IHC techniques. Strong supporting evidence for the presence of nAChRs in TRCs is provided by the effect of nAChR agonists and antagonists on the neural and behavioral responses in WT mice, Trpm5 KO mice and rats [ 2 , 3 ] and by our recent studies in STC-1 cells [ 8 ].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Although, the vast majority of the antibodies against nAChR subunits are considered to lack specificity [ 29 , 30 ], in this study nAChR expression in TRCs was confirmed by qRT-PCR, ISH and IHC techniques. Strong supporting evidence for the presence of nAChRs in TRCs is provided by the effect of nAChR agonists and antagonists on the neural and behavioral responses in WT mice, Trpm5 KO mice and rats [ 2 , 3 ] and by our recent studies in STC-1 cells [ 8 ].…”
Section: Discussionmentioning
confidence: 95%
“…STC-1 cell line is an established cell line of enteroendocrine cells of mouse small intestine. We have recently shown that exposing STC-1 cells to Nic acutely (24 h) or chronically (4 days) induced a differential increase in the expression of nAChR subunit mRNA and protein in a dose- and time-dependent fashion [ 8 ]. Here, we tested, if chronic Nic or ETOH exposure also alters nAChR mRNA expression in CV taste bud cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The changes in FIR were monitored under control conditions and after treating the cells with 0.01 to 1.0 mM nicotine or 10–50 mM ETOH in Ringer’s solution in the absence or presence of 50 μM Mec (Sigma-Aldrich). The FIR values in each cell were normalized to 1 under control conditions [ 7 , 8 , 14 ].…”
Section: Methodsmentioning
confidence: 99%